Incidence, Prevalence, and Mortality Trends in Chronic Obstructive Pulmonary Disease over 2001 to 2011: A Public Health Point of View of the Burden. (11th July 2016) - Doucet, Mariève; Rochette, Louis; Hamel, Denis
Abstract : Background . An increase of chronic obstructive pulmonary disease (COPD) prevalence was reported in Canada despite the decline of the main risk factor. Objectives . To estimate incidence, prevalence, and mortality of COPD from 2001 to 2011 and establish the COPD burden by the evaluation of the age-period-cohort effects on incidence trends and the comorbidities prevalence estimations. Methods . A retrospective population-based cohort was built using Quebec health administrative data. Change in trends was measured by relative percentage of changes and by joinpoint regression. After a descriptive analysis of the trends, an age-period-cohort analysis was performed on incidence rates. Results . Overall increase in prevalence along with a decrease of incidence and all-cause mortality was observed. Over time, all age-standardized trends were higher in men than women. Despite higher rates, the number of incident and prevalent cases in women exceeds men since 2004. The curve analysis by age groups showed over time a downshift for both sexes in incidence and all-cause mortality. Further analysis showed the presence of a cohort effect in women. Conclusion . The burden of COPD has risen over time. Women younger than 65 years old have been identified as at-risk group for healthcare planning.